2016
DOI: 10.1111/1750-3841.13356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of a New Model for Predicting the Growth of Clostridium perfringens in Cooked, Uncured Meat and Poultry Products under Isothermal, Heating, and Dynamically Cooling Conditions

Abstract: Clostridium perfringens type A is a significant public health threat and its spores may germinate, outgrow, and multiply during cooling of cooked meats. This study applies a new C. perfringens growth model in the USDA Integrated Pathogen Modeling Program-Dynamic Prediction (IPMP Dynamic Prediction) Dynamic Prediction to predict the growth from spores of C. perfringens in cooked uncured meat and poultry products using isothermal, dynamic heating, and cooling data reported in the literature. The residual errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The prevalence of Staphylococcus aureus on poultry meat products has been addressed, although most of the literature has focused on antibiotic resistance and typing of the isolates [ 63 , 64 , 65 ]. Although there are a few reports on the detection of Clostridium perfringens on poultry meat [ 61 ], most of the literature focuses on assessing and modeling its growth on meat after spore germination following the slaughtering process [ 66 , 67 , 68 ]. Lastly, the emergence of Aeromonas from poultry meat products as a vector of human infection has also been reported [ 10 ].…”
Section: The Major Bacterial Contaminants Of Poultry Meatmentioning
confidence: 99%
“…The prevalence of Staphylococcus aureus on poultry meat products has been addressed, although most of the literature has focused on antibiotic resistance and typing of the isolates [ 63 , 64 , 65 ]. Although there are a few reports on the detection of Clostridium perfringens on poultry meat [ 61 ], most of the literature focuses on assessing and modeling its growth on meat after spore germination following the slaughtering process [ 66 , 67 , 68 ]. Lastly, the emergence of Aeromonas from poultry meat products as a vector of human infection has also been reported [ 10 ].…”
Section: The Major Bacterial Contaminants Of Poultry Meatmentioning
confidence: 99%
“…SCD1 has been shown to be highly expressed in lung adenocarcinoma and was found to be important for cell proliferation, migration and invasion. Moreover, the study suggested SCD1 as a potential biomarker of lung adenocarcinoma [34]. A separate study showed delayed tumor growth in colorectal cancer mouse model on SCD1 inhibitor administration [35].…”
Section: Lipid Metabolism In the Tumor Microenvironmentmentioning
confidence: 99%
“…It should be stressed out, however, that calculating the inactivation parameters from dynamic temperature data requires more complicated numerical algorithms instead of standard non‐linear regression techniques (Corradini et al., 2008). Several studies, in the recent literature, have demonstrated the advantages of estimating kinetic parameters using non‐isothermal temperature conditions either during inactivation (Cattani et al., 2016; Corradini et al., 2005; Goula et al., 2018; Greiby et al., 2017; Huang, 2013; Kubo et al., 2018; Valdramidis et al., 2008) or microbial growth (Cornet et al., 2010; Huang, 2016; Huang & Vinyard, 2016; Longhi et al., 2017; Van Derlinden et al., 2008).…”
Section: Introductionmentioning
confidence: 99%